Tráfico e supressão no século XIX: o caso do Brigue Veloz - Marques, João Pedro (Africana Studia, 2020)
This paper studies the case of the Veloz, aPortuguese slave ship from Pernambuco (Brazil) captured on Benin River in 1837. This episode of Slave Trade suppression reveals from within the modus operandi of slave trade organizations that, at the time, were completely illegal. Furthermore, this case study illustrates several aspects of the Portuguese connivance in the odious commerce, of the high-handed suppression methods employed by British cruisers, and even of the African altitudes towards the Slave Trade.